Improvement of experimental animal handling skills for higher education laboratory technicians in Semarang Region Indonesia - Aditya Marianti; Wulan Christijanti; Wiwi Isnaeni; Badingatus Sholihah; Kartika Widyaningrum; Naufal Sebastian Anggoro; Yudi Priyanto (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
Laboratory technician skills in handling experimental animals are needed by the study program, which uses experimental animals in the lecture and research process. The Biology Laboratory of FMIPA UNNES has the resources to practice these skills. As the realization of the 3rd Dharma of the Tri Dharma of Higher Education, community service is carried out to improve the skills of higher education laboratory technicians both private and public universities in the city of Semarang in handling experimental animals. The method used is training in the form of hands-on practice. The animals used were mice and white rats. The trained practices were bioethics, maintenance techniques, handling, gavage, drawing blood, and vaginal smears of experimental animals. The participants consisted of 29 laboratory technicians from general medicine, dentistry, biology, biology education, pharmacy, and animal husbandry study programs. The training instructors consist of lecturers, technicians, and student assistants. The training was held for two days by implementing health protocols. As a result, the participants improved their skills. From the beginning, only 29,26% of participants had the knowledge and skills to handle experimental animals at the end of the training, increasing to 86.84%. It concludes that the participants have increased their knowledge and skills in handling experimental animals.